The Health Fitness Level in The Men Athlet Basket Ball in Christian Satya Wacana Salatiga Middle School - Fernandes, Andrian (Universitas Negeri Semarang (Unnes), 2019)
Basketball requires a good physical fitness condition, a good physical fitness needs an adequate exercise program, one of the popular exercise program is fartlek method. The purpose of this study is to know the effect of fartlek method that have had done for eight weeks (twice in a week) towards the VO2max of SMP Kristen Satya Wacana’s male basketball extracurricular. Based on the previous study about physical fitness, the participants of SMP Kristen Satya Wacana’s basketball extracurricular had a poor physical fitness proven by the result of cooper test that shown the VO2max on SMP Kristen Satya Wacana’s male basketball extracurricular was 29,19 ml⸱kg-1⸱min-1 (very poor).The VO2max was calculated using cooper test. The VO2max’s result on this research is 53,49 19 ml-kg-1-min-1, which is very good. T-tests were used to determine the result of pretest and postest, and the result of the vo2max is 26,03111±7,5 ml∙kg-1∙min-1 (p<0,05). Based on the result of this research, fartlek could be used to increase the VO2max of basketball male athletes of SMP Kristen Satya Wacana Salatiga.